THE USE OF VIDEO GAME TO IMPROVE STUDENTS WRITING SKILL OF PROCEDURE TEXT : a mixed method research in teaching procedure text of the 8th grade of junior high school in Waringinkurung - Pratama, Panji Ginanjar (2017)
Penelitian ini menggunakan metode mix method yang bertujuan untuk mencari tahu bagaimana penggunaan permainan video dalam meningkatkan kemampuan siswa dalam menulis teks prosedur dan presepsi siswa terhadap pengunaan permainan video dalam pembelajaran menulis teks prosedur. Penulis menemukan bahwa masalah utama dalam belajar bahasa Inggris siswa kelas 8 SMP di Waringinkurung yaitu menulis teks prosedur. Penulis mengharapkan dengan menggunakan permainan video berjudul Cooking Academy 3 dapat meninggkatkan kemampuan siswa dalam menulis teks prosedur. Peserta dalam penelitian ini adalah 20 orang siswa dari kelas 8 yang dipilih secara acak dari kelas A, B dan C SMPN 2 Waringinkurung pada tahun akademik 2016-2017. Penelitian ini menggunakan embedded design procedure dalam menggumpulkan data dengan menggukan data kualitatif yang didukung oleh data kuantitatif. Penelitian ini dilakukan dalam delapan pertemuan 2 x 46 menit, yang terdiri dari Pre-test, dua jenis kegiatan, dua kuis, dua kuisioner dan Post-test. Berdasarkan analisis data, skor rata-rata Pre-test siswa adalah 58,75, sementara Post-test 76,5. Peranserta siswa selama penelitian menunjukan bahwa mereka tertarik pada Cooking Academy 3 yang penulis gunakan dalam proses pengajaran. Berdasarkan hasil Pre-test and Post-test dengan menggunakan rumus presentase dasar ((58.75-76.5) x 100) / 58.75 menunjukkan peningkatan nilai siswa sebesar 30.3%. Hal ini menunjukan bahwa permainan video berjudul Cooking Academy 3 meningkatkan keterampilan siswa SMP dalam menulis teks prosedur.;---This is a mixed method research aiming finding out how video game improves students' skill in writing procedure text and the students' perceptions towards the use of video game in the teaching of writing procedure text. The author found that the main problem of the students of the 8th grade of junior high school in Waringinkurung is in writing procedure text. The author expected that Cooking Academy 3 video game would improve students' skill in writing skill procedure text. The participants of this reseach were 20 students of 8th grade chosen randomly from class A, B and C of SMPN 2 Waringinkurung in academic year of 2016/2017. This research used an embedded design procedure in collecting data using qualitative data, supported by the quantitative data. This research was conducted in eight meetings of 2x46 minutes, which included pre-test, two types of activities, two quizzes, two questionnaires, and post-test. According to the data analysis, pre test average score was 58.75, while the post test was 76.5. The students' participation during the treatment shows that they were interested and appreciated the Cooking Academy 3 video game that the author used in the teaching and learning process. Based on the pre-test and the post-test results, by using basic percentage formula of ((58.75-76.5) x 100) / 58.75, it could be concluded that there was an improvement of the students' score at 30.3%. This shows that the Cooking Academy 3 video game improves the junior high school students' skill in writing procedure text.